A Microcontroller Based Football Stadium Capacity Counter - Kafumbe, Said M. M.; Aldalaien, Muawya; Namwezi, Douce S.; Nibagwire, Clarisse N. (Asian Transactions, 2014)
In this work, a microcontroller based football stadium population counter was designed and implemented hands on using two active infrared sensor systems and the microcontroller system. The active infrared sensor systems consisted of an active sensing section whose task was to detect persons separately one after another using different entrance and exit points of the football stadium but also in robotics applications. From the sensing system a signal conditioning circuit was used in order to get a suitable and desirable output signal that the microcontroller could recognize and process. The microcontroller system, whose task was to determine the number of persons inside the stadium, consisted of one AT89C51 microcontroller outputting to the seven segment displays. By recognizing both the number of entering and leaving persons, the microcontroller executed a simple high level language program to determine the real number of spectators inside the stadium, and then displayed the obtained result on the seven segment displays. The counter system was designed with a capacity of 9999, although this could be improved through cascaded systems or by using more advanced embedded systems or robotics techniques.
Keywords: Microcontroller AT89C51; infrared transmitter; infrared receiver; signal conditioner; population counter; football stadium